Bone Mineral Disorders in Children with Predialysis Chronic Kidney Disease Correlates with Short Stature - Rania, Ghina; Puspitasari, Henny Adriani; Hidayati, Eka Laksmi; Hafifah, Cut Nurul (The Indonesian Society of Pediatric Gastroenterology, Hepatology, and Nutrition, 2024)
Background: The increasing prevalence of malnutrition and growth impairment among children with CKD could impact the prognosis and the preferred intervention. Therefore, this study aimed to identify the nutritional status of children with CKD and its relating factors. Method: A cross-sectional study was conducted in a tertiary, national-referral teaching hospital in Jakarta. Sociodemographic and laboratory data were obtained from medical records. Body weight and height of participants were measured using digital scale and stadiometer, respectively. Growth and nutritional status indicators such as BMI-for-age, weight-for-height, height for age, and weight for age were quantified and plotted using WHO Anthro and Anthroplus application. Result: A total of 18 participants aged 3-17 years old with CKD stage 3 – 5 were included in this study. BMI measurements showed a z-score average of -1.02, while the mean z-score for height-for-age was of -2.71. Our study demonstrated a significant association between the height-for-age and mineral bone in children with CKD (p = 0.005). However, we found no association between mineral bone disorder with other indicators of nutritional status. Furthermore, our study also found no significant relation between nutritional status and other influencing factors including the stage of CKD, duration of CKD, age, gender, primary etiological factor, hypertension, anemia, age, familial economic status, disease duration, and parental education level demonstrates no significant correlation (p > 0.05). Conclusion: Children with stage 3 – 5 CKD in the pre-dialysis phase are shown to be underweight and short statured but with normal nutritional status. Mineral bone disorder was revealed to be significantly associated with height-for-age in children with CKD.